Evaluation of the protective capacity of baseball helmets for concussive impacts. Issue 4 (11th March 2016) - Post, Andrew; Karton, Clara; Blaine Hoshizaki, T.; Gilchrist, Michael D.; Bailes, Julian
Abstract : The purpose of this research was to examine how four different types of baseball helmets perform for baseball impacts when performance was measured using variables associated with concussion. A helmeted Hybrid III headform was impacted by a baseball, and linear and rotational acceleration as well as maximum principal strain were measured for each impact condition. The method was successful in distinguishing differences in design characteristics between the baseball helmets. The results indicated that there is a high risk of concussive injury from being hit by a ball regardless of helmet worn.